Identification of Genes Encoding Antimicrobial Proteins in Langerhans Cells - Oulee, Aislyn; Ma, Feiyang; Teles, Rosane M. B.; de Andrade Silva, Bruno J.; Pellegrini, Matteo; Klechevsky, Eynav; Harman, Andrew N.; Rhodes, Jake W.; Modlin, Robert L. (Frontiers in Immunology, 2021)
Langerhans cells (LCs) have a dendritic morphology as well as potent antigen presenting function similar to dendritic cells (DCs), that reside in the epidermis where they are poised to mount an antimicrobial response against microbial pathogens invading from the outside environment. To elucidate potential pathways by which LCs contribute to host defense, we mined published LC transcriptomes deposited in GEO and the scientific literature for genes that participate in antimicrobial responses. Overall, we identified 30 genes in LCs that encode proteins that contribute to antimicrobial activity. Of the 22 genes identified in transcriptomes, eight genes were upregulated in TNF-treated LCs and 15 genes were preferentially expressed in LCs vs other myeloid cell types. In addition, 11 of the 30 genes encode chemokines, which mediate both antimicrobial and inflammatory responses. Of these, CCL22 was detected in six of nine transcriptomes and in murine LCs during maturation. Of the 30 total genes, 29 encode peptides with antibacterial activity and 23 display antibacterial activity against Staphylococcus aureus, which is the leading cause of skin infections. Thus, this study illustrates that LCs, consistent with their anatomical location, are programmed to mount an antimicrobial response against invading pathogens.